Comparison of Coagulation Parameters between Severe and Non-severe COVID-19 Patients Treated in a Tertiary Hospital in Indonesia - Fianza, Pandji Irani; Prihatni, Delita; Purnama, Dasep Bambang (International Journal of Integrated Health Sciences, 2023)
Objective: To determine the differences in coagulation features in patients with severe versus non-severe COVID-19. Method: During the period of the study from July 2020 to June 2021, 371 COVID-19 patients were treated at Dr. Hasan Sadikin Hospital. These patients were divided into two groups based on the WHO critera into severe COVID-19 with clinical signs such as severe acute respiratory syndrome to respiratory failure and non-severe cases with no respiratory symptoms. Data analyzed were Prothrombin Time (PT), Activated Partial Thromboplastin Time (aPTT), International Normalized Ratio (INR), fibrinogen, D-dimer, and platelet count.Results: Median INR was significantly higher in patients with severe cases than in non-severe cases (1.04 vs. 0.94, p<0.001), which was also true for median PT (12.3 vs. 12.0 sec, p=0.030) and median fibrinogen (522 vs. 428.5 mg/dl, p=0.004). Similarly, the median D-dimer was significantly higher in severe patients (1.91 vs. 0.75 mg/dl, p<0.001). Median aPTT and platelet count were in normal limits for both severe and non-severe COVID-19 patients (28.6 vs. 29.15 sec, p>0.652 and 246 vs. 242 x103/mm3, p>0.924, respectively).Conclusions: The INR, PT, fibrinogen, and D-dimer can be considered as features that can be used to predict the severity of the disease and to choose the proper treatment for COVID-19 patients.